Respuesta :
Answer:
Step-by-step explanation:
[tex]6-[\frac{2}{5}+\{3\frac{1}{4}-(\frac{3}{8}+\frac{1}{2})\}]\\\\=6-[\frac{2}{5}+\{3\frac{1}{4}-(\frac{3}{8}+\frac{1*4}{2*4})\}]\\\\=6-[\frac{2}{5}+\{\frac{13}{4}-(\frac{3}{8}+\frac{4}{8})\}\\\\=6-[\frac{2}{5}+\{\frac{13*2}{4*2}-\frac{7}{8}\}]\\\\=6-[\frac{2}{5}+\{\frac{26}{8}-\frac{7}{8}\}]\\\\=6-[\frac{2}{5}+\frac{19}{8}]\\\\=6-[\frac{2*8}{5*8}+\frac{19*5}{8*5}]\\\\=6-[\frac{16}{40}+\frac{95}{40}]\\\\=6-\frac{111}{40}\\\\=\frac{6*40}{1*40}-\frac{111}{40}\\\\=\frac{240}{40}-\frac{111}{40}\\\\[/tex]
=129/40
= [tex]3\frac{9}{40}[/tex]
=